The Bramble - Nordling, Lee; Zick, Bruce (Minneapolis : Carolrhoda Books, 2013)
Cameron desperately wants to play tag with the older boys, who laugh at him for not being able to touch any of them, but when he tumbles into a bramble Cameron finds himself in another world where his talents are appreciated.
Keywords: Ability -- Fiction; Imaginary creatures -- Fiction; Tag games -- Fiction